El Salvador : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
KEY ISSUES Focus: The main themes centered on tackling macroeconomic vulnerabilities and improving the medium-term outlook by achieving an ambitious fiscal adjustment while protecting social spending, creating an environment for higher private sector-led growth, and building a robust financial sector. Main policy issues -- A reduction in the fiscal deficit of 3 1\2 percent of GDP is needed over the next three years to place public debt on a sustainable path to maintain access to market financing on favorable terms. This adjustment should be accompanied by well- targeted social spending to protect the most vulnerable and continued progress in lessening inequality. -- A broad strategy is also needed to reduce the growing imbalances in the pension system and restore its sustainability for future generations. In this regard, a broad- based dialog across all segments of Salvadoran society is needed to build support for a reform that should include an increase in the retirement age and introduce a progressive taxation of benefits. Steps are also needed to further strengthen public financial management to mitigate key fiscal risks, including by enhancing expenditure monitoring and control (to avoid future spending arrears) and recording contingent fiscal liabilities transparently in the fiscal accounts. -- The authorities' goal of raising potential growth to 3 percent while reducing inequality will require substantial supply-side measures to enhance productivity and competitiveness. These should aim to reduce red-tape, increase access to credit, upgrade infrastructure, provide access to and lower the cost of energy, and diversifying the economy. The FOMILENIO II grant from the U.S. provides a valuable opportunity to catalyze such growth-enhancing reforms. -- Banking indicators appear sound, a product of prudent supervision and regulation. Nonetheless, there is scope to further strengthen the institutional underpinnings for financial stability by upgrading the legal framework for bank resolution and by creating an appropriate liquidity safety net for banks.